Intersémioticité et interethnicité dans le De Etruria Regali Libri Septem de Thomas Dempster - Jean Berton (Caliban: French Journal of English Studies, 2017)
Born in 1579 to a Roman Catholic family in Aberdeenshire, educated at Cambridge and Paris, Thomas Dempster became a travelling lecturer in France and Italy, where the Duke of Tuscany gave him a position at Pisa. Soon Dempster was commissioned by his patron to produce a report on what had been discovered for two or three generations in Tuscany, and in 1620 he handed over to the Duke his "Of the Kingdom of Etruria" (published in 1723). Emulating his contemporary "historian" fellows, Dempster filled the gaps with what he thought must be the truth. However, when reading the chapters of the seven books, written in Latin, one can find likely hints at what Scotland was in the 1610s, suspect parallels between the Etruscan language found in fragments and ogham, wonder at comparisons between Etruscan and Scottish boats, and feel driven to weigh the battle of Lake Trasimene (217 B.C.) against that of Nechtansmere (685 A D)… So much so that we are allowed to question Dempster’s intentions, particularly on the colonisation issue.